Breast tumor kinase (Brk/PTK6) is a mediator of hypoxia-associated breast cancer progression - Regan Anderson, Tarah M. (2013)
Basal-type triple-negative breast cancers (TNBC) are aggressive and difficult to treat relative to luminal type breast cancers. TNBC often express abundant Met receptors and are enriched for transcriptional targets regulated by hypoxia inducible factor 1-alpha (HIF-1α), which independently predicts cancer relapse and increased risk of metastasis. Brk/PTK6 is a critical downstream effector of Met signaling and required for HGF-induced cell migration. Herein, we examined the regulation of Brk by HIFs in TNBC in vitro and in vivo. Brk mRNA and protein levels are upregulated strongly in vitro by hypoxia, low glucose and reactive oxygen species. In HIF-silenced cells, Brk expression relied upon both HIF-1α and HIF-2α, which we found to regulate BRK transcription directly. HIF-1α/2α silencing in MDA-MB-231 cells diminished xenograft growth and Brk re-expression reversed this effect. These findings were pursued in vivo by crossing WAP-Brk (FVB) transgenic mice into the MET(mut) knock-in (FVB) model. In this setting, Brk expression augmented MET(mut)-induced mammary tumor formation and metastasis. Unexpectedly, tumors arising in either MET(mut) or WAP-Brk X MET(mut) mice expressed abundant levels of Sik, the mouse homolog of Brk, which conferred increased tumor formation and decreased survival. Taken together, our results identify HIF-1α/2α as novel regulators of Brk expression and suggest that Brk is a key mediator of hypoxia-induced breast cancer progression. Targeting Brk expression or activity may provide an effective means to block the progression of aggressive breast cancers.